Eccentric overload during resistance exercise: a stimulus for enhanced satellite cell activation - Wehrstein, Michaela; Schöffel, Axel; Weiberg, Nadine; Gwechenberger, Thomas; Betz, Theresa Maria; Rittweg, Mareike; Parstorfer, Mario; Pilz, Maximilian; Friedmann-Bette, Birgit (Medicine and science in sports and exercise, 2022)
Satellite cells (SC) are of importance for muscular adaptation to various forms of exercise. A single bout of high-force eccentric exercise has been shown to induce SC activation and, for electrically stimulated exercise, SC differentiation. - Purpose - This study aimed to assess if one bout of concentric/eccentric exercise with damaging eccentric overload (CON/ECC+) provides a sufficient stimulus to induce SC activation, proliferation, and differentiation. - Methods - Biopsies from the vastus lateralis muscle of recreationally active men were obtained in the rested condition and again from the contralateral leg 7 d after exhaustive concentric/eccentric (CON/ECC) (n = 15) or CON/ECC+ (n = 15) leg extension exercise and in a nonexercising control group (CG) (n = 10). Total SC number (Pax7+), activated (Pax7+/MyoD+), and differentiating (myogenin+) SCs, fiber type distribution, and myofibers expressing neonatal myosin heavy chain (MHCneo) were determined immunohistochemically. Creatine kinase and myoglobin were measured in venous blood. Isokinetic strength tests were repeatedly conducted. - Results - Significant increases in creatine kinase and myoglobin (P = 0.001) indicated myofiber damage, whereas maximal strength was not impaired. Only after CON/ECC+, SC content (P = 0.019) and SC related to type II fibers (P = 0.011) were significantly increased. A significant increase in the proportion of activated SCs occurred after CON/ECC+ only (P = 0.003), the increase being significantly (P < 0.05) different from the changes after CON/ECC and in CG. The number of differentiating SC and MHCneo remained unchanged. - Conclusions - Eccentric overload during leg extension exercise induced significant SC activation, increases in SC content and in SC number related to type II myofibers. However, there were no signs of increased SC differentiation or formation of new myofibers.